About bodies, writing and dance literacy: experiences with Motifs at school (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This text reports on a case study carried out with students from a public school in São Paulo in which a proposal for dance literacy was tried out using Motif Notation, a notation system created by researchers Ann Hutchinson Guest (1918-2022) and Valerie Preston-Dunlop (1930-), former pupils of researcher Rudolf Laban (1879-1958). It was based on action research methodology (Thiollent, 2011), the data was collected in workshops held by videoconference and the conclusions were that it was possible to encourage proposals for dance literacy, the acquisition of characteristics of this language by the children and the creation of a choreographic composition.
Keywords: dance literacy; body; writing; Motif Notation; Rudolf Laban